Continuous glucose monitoring for automatic real-time assessment of eating events and nutrition: a scoping review - Brummer, Julian; Glasbrenner, Christina; Hechenbichler Figueroa, Sieglinde; Koehler, Karsten; Höchsmann, Christoph (Frontiers in Nutrition, 2024)
Background: Accurate dietary assessment remains a challenge, particularly in free-living settings. Continuous glucose monitoring (CGM) shows promise in optimizing the assessment and monitoring of ingestive activity (IA, i.e., consumption of calorie-containing foods/beverages), and it might enable administering dietary Just-In-Time Adaptive Interventions (JITAIs). Objective: In a scoping review, we aimed to answer the following questions: 1) Which CGM approaches to automatically detect IA in (near-)real-time have been investigated? 2) How accurate are these approaches? 3) Can they be used in the context of JITAIs? Methods: We systematically searched four databases until October 2023 and included publications in English or German that used CGM-based approaches for human (all ages) IA detection. Eligible publications included a ground-truth method as a comparator. We synthesized the evidence qualitatively and critically appraised publication quality. Results: Of 1,561 potentially relevant publications identified, 19 publications (17 studies, total N=311; for 2 studies, 2 publications each were relevant) were included. Most publications included individuals with diabetes, often using meal announcements and/or insulin boluses accompanying meals. Inpatient and free-living settings were used. CGM-only approaches and CGM combined with additional inputs were deployed. A broad range of algorithms was tested. Performance varied among the reviewed methods, ranging from unsatisfactory to excellent (e.g., 21% vs. 100% sensitivity). Detection times ranged from 9.0 to 45.0 minutes. Conclusion: Several CGM-based approaches are promising for automatically detecting IA. However, response times need to be faster to enable JITAIs aimed at impacting acute IA. Methodological issues and overall heterogeneity among articles prevent recommending one single approach; specific cases will dictate the most suitable approach.